2017
DOI: 10.1016/j.semarthrit.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated BMI and antibodies to citrullinated proteins interact to increase rheumatoid arthritis risk and shorten time to diagnosis: A nested case–control study of women in the Nursesʼ Health Studies

Abstract: Objective Overweight/obesity and anti-citrullinated protein antibodies (ACPA) increase RA risk. We investigated the relationship between body mass index (BMI) and ACPA, tested for an interaction between BMI and ACPA for RA risk, and examined effects of BMI and ACPA on time to RA diagnosis. Design Within the Nurses’ Health Studies, blood samples were collected before diagnosis from medical record-confirmed incident RA cases and matched controls. Multiplex assays measured seven ACPA subtypes (biglycan, cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…33 Obesity has been identified as a risk factor for several other autoimmune diseases, including rheumatoid arthritis, psoriasis, psoriatic arthritis, inflammatory bowel disease, and sarcoidosis. 16,17,3439 Murine models of SLE-prone mice (NZB/WF1 females) also support the hypothesis that obesity may be associated with increased SLE risk, as these mice have higher body weight and greater visceral fat compared to control mice. 40 …”
Section: Discussionmentioning
confidence: 69%
“…33 Obesity has been identified as a risk factor for several other autoimmune diseases, including rheumatoid arthritis, psoriasis, psoriatic arthritis, inflammatory bowel disease, and sarcoidosis. 16,17,3439 Murine models of SLE-prone mice (NZB/WF1 females) also support the hypothesis that obesity may be associated with increased SLE risk, as these mice have higher body weight and greater visceral fat compared to control mice. 40 …”
Section: Discussionmentioning
confidence: 69%
“…Most studies on the effects of obesity on risk to develop RA have demonstrated a certain increased risk for RA in individuals with obesity [109,110]. Dietary factors have for a long time been in the focus of many studies on development and disease course of RA, but results have in most cases remained inconclusive and difficult to reproduce.…”
Section: Effects Of Obesity Diet and Alcoholmentioning
confidence: 99%
“…The Swedish Obese Subjects (SOS) study is a longitudinal non-randomized controlled study designed to examine the effect of bariatric surgery on obesityassociated morbidity and overall mortality (24)(25)(26). In this cohort of subjects with obesity, we have previously analysed the effect of bariatric surgery on the future development of RA, since obesity is thought to be a risk factor for the development of the disease, in particular if combined with other factors (27,28). However, we were not able to detect any association between bariatric surgery and the incidence of RA (29).…”
mentioning
confidence: 99%